The Determinants of financial inclusion in Colombian microenterprises - Hernández García, Edwin Arbey (2023)
Objective: to find some determinants of financial inclusion in Colombian microenterprises for the period 2015 and 2017. Method: financial inclusion is defined from its four dimensions (access, use, quality, and wellness), and econometric probability models. Logit type is estimated, such that it allows an approximation to the determinants to effectively increase the financial inclusion of microenterprises. Results: It was found that education, the separation of household finances from microenterprise finances, business formality and Information technology and communications perform a fundamental role to comprehensively increase financial inclusion, that is, in all its dimensions. Conclusions: higher levels of financial education and knowledge of managing information technologies, financial inclusion grows in an integral way from the demand for financial services.